Treating Suicidal Thoughts and Behaviors Within an Emotional Disorders Framework: Acceptability and Feasibility of the Unified Protocol in an Inpatient Setting. (July 2017) - Bentley, Kate H.; Sauer-Zavala, Shannon; Cassiello-Robbins, Clair F.; Conklin, Laren R.; Vento, Stephanie; Homer, Danyele
We provide a theoretical rationale for applying a transdiagnostic, shared mechanism treatment (the Unified Protocol for Transdiagnostic Treatment of Emotional Disorders [UP]) to suicidal thoughts and behaviors. We also present results from a proof of concept study examining the feasibility and acceptability of adding a modified UP to treatment as usual (TAU) in an inpatient setting for individuals reporting a recent suicide attempt or active suicidal ideation. Participants ( N = 12) were randomly assigned to receive UP + TAU or TAU alone. Findings indicate good feasibility and acceptability of the adjunctive intervention. Among participants who were responsive to contact attempts postdischarge ( n = 6), there were no observable differences in suicidal thoughts or behaviors during a 6-month follow-up. This application represents a promising initial extension of a cognitive-behavioral, emotion-focused treatment to suicidal individuals within an inpatient setting. Future studies adequately powered to speak to efficacy of the modified UP intervention are warranted.